Impactos operacionais e resiliência de aeroportos a condições meteorológicas adversas - Abrão Junior, Fued (2018)
The thesis explores the impact of adverse meteorological conditions on airport operations in terms of flights canceled during the landing phase. In a broader context, climate change may be intensifying these impacts. The analysis investigates the probable meteorological parameters behind cancellations at four important Brazilian airports, identifying which ones were involved in the highest rates of cancellations, quantifying tariff collection losses due to these parameters, classifying the relative degree of impact, drawing inferences about the resilience of extant infrastructure and making comparisons between the airports, proposing measures for the least resilient airport and estimating the degree to which its resilience could be increased by implementing them. Replicable features of this study include the analytical procedures, indicators of the degree of relative impact of cancellations due to adverse conditions, and the airport infrastructure resilience index. It is concluded that the operational impacts (i.e., cancellations) are not only a consequence of adverse meteorology, but of existing infrastructure conditions. Since climate change projections indicate that extreme events will become more frequent, airports that are already impacted will be even more so in the future, reducing their viability. Increasing the resilience of such airports is possible, at least for the most critical ones, which would allow operational continuity, albeit under new standards, in a climate change scenario.